The Association of Coloproctology of Great Britain and Ireland consensus guidelines in emergency colorectal surgery. (27th February 2021) - Miller, Andrew S.; Boyce, Kathryn; Box, Benjamin; Clarke, Matthew D.; Duff, Sarah E.; Foley, Niamh M.; Guy, Richard J.; Massey, Lisa H.; Ramsay, George; Slade, Dominic A. J.; Stephenson, James A.; Tozer, Phil J.; et al.
Abstract: Aim: There is a requirement for an expansive and up to date review of the management of emergency colorectal conditions seen in adults. The primary objective is to provide detailed evidence‐based guidelines for the target audience of general and colorectal surgeons who are responsible for an adult population and who practise in Great Britain and Ireland. Methods: Surgeons who are elected members of the Association of Coloproctology of Great Britain and Ireland Emergency Surgery Subcommittee were invited to contribute various sections to the guidelines. They were directed to produce a pathology‐based document using literature searches that were systematic, comprehensible, transparent and reproducible. Levels of evidence were graded. Each author was asked to provide a set of recommendations which were evidence‐based and unambiguous. These recommendations were submitted to the whole guideline group and scored. They were then refined and submitted to a second vote. Only those that achieved >80% consensus at level 5 (strongly agree) or level 4 (agree) after two votes were included in the guidelines. Results: All aspects of care (excluding abdominal trauma) for emergency colorectal conditions have been included along with 122 recommendations for management. Conclusion: These guidelines provide an up to date and evidence‐based summary of the current surgical knowledge in the management of emergency colorectal conditions and should serve as practical text for clinicians managing colorectal conditions in the emergency setting.